(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article analyzes the neuropsychological mechanisms that affect the formation of speech motorics in preschool children with hearing impairments. Factors such as sensorimotor integration, phonological processes, lateralization, articulatory control, and compensatory brain functions are scientifically covered. Also, modern pedagogical and speech therapy technologies aimed at the development of speech motorics are scientifically described